Bilateral scapular fractures in adults - Tuček, Michal (Springer-Verlag, 2013)
PURPOSE: Bilateral scapular fracture is a very rare injury. Most of these fractures result from electrical shock or epileptic seizure. We treated six patients with such injuries, all of them caused by direct violence. The aim of this study was to report on the patients and to present an overview of the cases published so far. METHODS: Between January 2011 and August 2012, we treated six patients with bilateral scapular fractures (four men and two women, age range 20–78 years). Another 11 cases were found in the literature. All cases were analysed in terms of injury mechanism, fracture pattern and the manner of diagnosis. RESULTS: Our six patients increased the total number of recorded cases to 17 and the number of patients with traumatic bilateral scapular fractures from four to ten. In five of our cases, the injuries were classified as being the result of high-energy trauma. Computed tomography (CT) examination of the affected scapulae was performed in all six cases, in five in combination with 3D CT reconstruction; in one polytraumatised female patient, only axial CT scans were obtained. In all five high-energy trauma cases, bilateral fracture of the scapular body was recorded, of which one was classified as open. Four of the 11 cases found in the literature were caused by direct violence: in six patients, the fractures resulted from muscle spasms associated with epileptiform seizure or electrical shock, and one patient suffered a pathological fracture associated with amyloidosis. The most frequently recorded fracture in all 17 patients (34 fractures) was of the scapular body, i.e. 24 fractures, followed by 12 fractures of the glenoid fossa. CONCLUSION: According to data in the literature, bilateral scapular fracture is a rare injury. One reason may be that the potential incidence is often neglected. With the increasing number of patients with polytrauma, the potential for scapular fracture should always be taken into account, together with the fact that this injury may be bilateral. Of vital importance in diagnosing these injuries is CT scanning, including 3D CT reconstructions.